Surveillance of Shiga toxin-producing Escherichia coli and Campylobacter spp. in wild Japanese deer (Cervus nippon) and boar (Sus scrofa) - TOMINO, Yoshiyuki; ANDOH, Masako; HORIUCHI, Yuta; SHIN, Jiye; AI, Ryunosuke; NAKAMURA, Takaki; TODA, Mizuki; YONEMITSU, Kenzo; TAKANO, Ai; SHIMODA, Hiroshi; MAEDA, Ken; KODERA, Yuuji; et al. (Journal of Veterinary Medical Science, 2020)
Increasing game meat consumption in Japan requires the dissemination of safety information regarding the presence of human pathogens in game animals. Health information regarding the suitability of these animals as a meat source is not widely available. In this study, we aimed to evaluate the safety of game meat and detect potential human pathogens in wild deer (Cervus nippon) and boar (Sus scrofa) in Japan. Fecal samples from 305 wild deer and 248 boars of Yamaguchi, Kagoshima, and Tochigi prefectures collected monthly for 2 years were examined for the prevalence of Shiga toxin-producing Escherichia coli (STEC) and Campylobacter spp. STEC was isolated from 51 deer consistently throughout the year and from three boars; O-antigen genotype O146, the expression of stx2b, and eaeA absence (n=33) were the major characteristics of our STEC isolates. Other serotypes included the medically important O157, stx2b or stx2c, and eaeA-positive (n=4) and O26, stx1a, and eaeA-positive strains (n=1). Campylobacter spp. were isolated from 17 deer and 31 boars. Campylobacter hyointestinalis was the most common species isolated from 17 deer and 25 boars, whereas Campylobacter lanienae and Campylobacter coli were isolated from three and two boars, respectively. Seasonal trends for the isolation of these bacteria were not significant. This study demonstrates that wild game animals carry human pathogens; therefore, detailed knowledge of the safe handling of game meat is needed to prevent foodborne infections.